1983
DOI: 10.1159/000176724
|View full text |Cite
|
Sign up to set email alerts
|

Manganese in Infant Formulas and Learning Disability

Abstract: The concentration of manganese in the hair of normal newborn infants was found to increase significantly from 0.19 µg/g at birth to 0.965 µg/g at 6 weeks of age and 0.685 µg/g at 4 months when they were fed infant formula. There was an insignificant increase to 0.330 µg/g at age 4 months in breast-fed infants. After this age there was a slow decline in hair manganese to 0.268 µg/g in normal children at age 8 years and 0.434 in learning disabled (hyperactive) children. This is the third study reporting elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
55
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 14 publications
7
55
0
Order By: Relevance
“…Thus, Finley's findings (19) are probably not comparable to the situation of our patient who received up to 5 years of manganese loading from ingested water. In at least one study of infants, significant increases in hair manganese levels were found among young infants fed infant formulas containing relatively high amounts of manganese compared to hair manganese levels in infants fed breast milk, which contains relatively little manganese (22). Thus, bioavailability of ingested manganese in infants and children may be quite different from that in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Finley's findings (19) are probably not comparable to the situation of our patient who received up to 5 years of manganese loading from ingested water. In at least one study of infants, significant increases in hair manganese levels were found among young infants fed infant formulas containing relatively high amounts of manganese compared to hair manganese levels in infants fed breast milk, which contains relatively little manganese (22). Thus, bioavailability of ingested manganese in infants and children may be quite different from that in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies reported high hair Mn (MnH) levels in learning-disabled and hyperactive children when compared with controls (Barlow 1983;Collipp et al 1983;Pihl and Parkes 1977).…”
mentioning
confidence: 99%
“…Furthermore, no Mn exposure source was identified, although Collipp et al (1983) raised the hypothesis that it was infant formula with high Mn. The association between Mn exposure and children's hyperactive behaviors remains plausible because the dopaminergic and GABAergic systems that play a role in hyperactivity in children (Li et al 2006;Sagvolden et al 2005) are also vulnerable to Mn (Fitsanakis et al 2006).…”
mentioning
confidence: 99%
“…More recently, the developmental neurotoxicity of manganese has emerged as a significant public health concern. In several small epidemiologic studies of children, manganese hair levels are associated with ADHD (27)(28)(29). Developmental exposure to manganese in laboratory animals is associated with hyperactivity (30).…”
Section: Manganesementioning
confidence: 99%